Trio, a novel high fecundity allele: I. Transcriptome analysis of granulosa cells from carriers and non-carriers of a major gene for bovine ovulation rate - Kamalludin, Mamat Hamidi; Guerra, Alvaro Garcia; Wiltbank, Milo C.; Kirkpatrick, Brian W. (Society for the Study of Reproduction, 2018)
A major gene for bovine ovulation rate has been mapped to a 1.2 Mb region of chromosome 10. Screening of coding regions of positional candidate genes within this region failed to reveal a causative polymorphism, leading to the hypothesis that the phenotype results from differences in candidate gene expression rather than alteration of gene structure. This study tested differences in expression of positional candidate genes in granulosa cells between carriers and noncarriers of the high fecundity allele, as well as characterizing differences in the transcriptomic profile between genotypes. Five carriers and five noncarriers, female descendants of "Trio," a carrier of the high fecundity allele were initially used in an RNA-seq analysis of gene expression. Four of ten samples were contaminated with theca cells, so that six samples were used in the final analysis (three of each genotype). Of 14 973 genes expressed, 143 were differentially expressed (false discovery rate P < 0.05) in carriers versus noncarriers. Among the positional candidate genes, SMAD6 was 6.6-fold overexpressed in the carriers compared to noncarriers (P < 5 × 10-5). This result was replicated in an independent group of 12 females (7 carriers and 5 noncarriers) using quantitative real-time PCR; SMAD6 was 9.3-fold overexpressed in carriers versus noncarriers (P = 1.17 × 10-6). Association of overexpression of SMAD6, an inhibitor of the BMP/SMAD signaling pathway, with high ovulation rate corresponds well with disabling mutations in ligands (BMP15 and GDF9) and a receptor (BMPR1B) of this pathway that cause increased ovulation rate in sheep.